OPEC, Unconventional Oil and Climate Change - On the importance of the order of extraction - Hassan Benchekroun; Gerard van der Meijden; Cees Withagen (Tinbergen Institute, 2020)
We show that OPEC's market power contributes to climate change by enabling producers of relatively expensive and dirty oil to start producing before OPEC reserves are depleted. We examine the importance of this extraction sequence effect by calibrating and simulating a cartel-fringe model of the global oil market. While welfare net of climate damage under the cartel-fringe equilibrium can be significantly lower than under a first-best outcome, almost the entire welfare loss is due to the sequence effect of OPEC's market power. In our benchmark calibration, the cost of the sequence effect amounts to 15 trillion US, which corresponds to 97 percent of the welfare loss. Moreover, we find that an increase in non-OPEC oil reserves decreases global welfare. In a counterfactual world without non-OPEC oil, global welfare would be 13 trillion US higher, 10 trillion US of which is due to lower climate damages.
Keywords: Q31; Q42; Q54; Q58; 330; cartel-fringe; climate policy; non-renewable resource; Her?ndahl rule